(untitled) (Research, Society and Development, 2020)
Seventeen common bean genotypes of the Carioca commercial group, among cultivars and advanced strains, were evaluated for agronomic performance in the 2016/2017 crop, with the objective of evaluating their potential for future indications of cultivation in the cerrado-pantanal ecotone region. The experiment was conducted from April to August in the experimental area of the State University of Mato Grosso do Sul - University Unit of Aquidauana, in a randomized block design with three replications. The experimental plots consisted of four rows of plants with 4.0 meters in length spaced between each other of 0.50 m, being considered useful area the two central rows. The genotypes were evaluated for cycle, plant architecture, production components, grain yield, tolerance to plant lodging and diseases. Since most of the genotypes evaluated obtained unsatisfactory performance, it is inferred that the edaphoclimatic conditions interfered with their real genetic potentials. On the other hand, the genotypes that presented the best grain quality in terms of commercial acceptance were cnfc 16242 and CNFC 16066, showing at first, potential for production.